2013
DOI: 10.1088/0004-637x/771/2/78
|View full text |Cite
|
Sign up to set email alerts
|

RECOMBINATION RATE COEFFICIENTS OF BORON-LIKE Ne

Abstract: Recombination of Ne 5+ was measured in a merged-beam type experiment at the heavy-ion storage ring CRYRING. In the collision energy range 0-110 eV resonances due to 2s 2 2p → 2s2p 2 (Δn = 0) and 2s 2 2p → 2s 2 3l (Δn = 1), core excitations were observed. The experimentally derived rate coefficients agree well with the calculations obtained using AUTOSTRUCTURE. At low energies, recombination is dominated by resonances belonging to the spinforbidden 2s2p 2 ( 4 P J )nl series. The energy-dependent rate coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…One line of atomic physics research at heavy ion-storage rings aims at providing accurate atomic data, i.e., absolute cross sections for PR and EII, for applications in astrophysics and plasma physics (for the most recent published results see Mahmood et al 2013. Since these activities have been repeatedly reviewed before (Savin 2007, Schippers 2009a, Schippers 2012, Hahn 2014 they are only briefly mentioned here.…”
Section: Atomic Data For Astrophysics and Plasma Physicsmentioning
confidence: 99%
“…One line of atomic physics research at heavy ion-storage rings aims at providing accurate atomic data, i.e., absolute cross sections for PR and EII, for applications in astrophysics and plasma physics (for the most recent published results see Mahmood et al 2013. Since these activities have been repeatedly reviewed before (Savin 2007, Schippers 2009a, Schippers 2012, Hahn 2014 they are only briefly mentioned here.…”
Section: Atomic Data For Astrophysics and Plasma Physicsmentioning
confidence: 99%
“…Owing to the high electron energies and small cross sections, the electron recombination rate between free electrons and 1+ ions is deemed small in comparison to the electron impact excitation rate. 19 Excitation by photon re-absorption can be neglected due to low neutral and 1+ densities, i.e., ECRIS plasmas can be considered optically thin. Yet another reaction, in which the ion ends up to an excited state, is charge exchange between a highly charged ion and neutral atom.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…vrel is the relative velocity between electron and ion [39]. By fitting the measured DR spectrum from 0.38 eV up to 5 eV with six resonances associated to 2s 2 2p 5 ( 2 P1/2) nl, where n = 18,19,20,21,22. The resonance energies and strengths are obtained and listed in Table 1 The uncertainty of the experimental recombination rate coefficients is estimated to be about 30%, an uncertainty of 10% due to combination of counting statistics, electron and ion beam currents, and interaction length, and an uncertainty of 20% due to the electron density distribution profile and also the position of the ion beam in this profile.…”
Section: ( ) ( ) ( )mentioning
confidence: 99%
“…However, for DR in the photoionized plasma which located in the low-energy range, the modeling is mostly based on theoretical predictions and calculations,and many theories cannot provide the sufficiently precise DR rate coefficients [16]. In addition, the recent experimental approach for low energy range DR investigation has also shown that earlier computations of low temperature DR rate coefficients are not accurate [17][18][19]. To model the line emission, thermal and ionization structures of plasmas, the astrophysicists required accurate bench-mark atomic data from electron-ion recombination experiments [20].…”
Section: Introductionmentioning
confidence: 99%